2015
DOI: 10.1142/s1793292015500733
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Iron Oxide Nanoclusters with Enhanced Magnetization and Their Applications in Pulsed Magneto-Motive Ultrasound Imaging

Abstract: We report here a facile synthetic approach for preparing water-soluble Fe 3 O 4 nanoparticle (NP) clusters with tunable size distribution and magnetic properties. The primary NP sizes were controlled by tuning the nucleation and growth rates with temperature and ligand concentration while the nanocluster sizes were manipulated by controlling interparticle interactions. We have investigated the size control of clusters as well as individual primary NPs via dynamic light scattering (DLS) analysis and transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…While keeping the superparamagnetic behavior, the synthesis of multicore particles proved to be a promising solution for magnetics based imaging, therapeutics, and sensing to improve the manifold magnetic response of particles [40,[52][53][54][55][56]. Magnetic nanoparticle clusters embedded in a polymer shell, to sum the magnetic moments of each nanoparticle, were made applying in situ coprecipitation by using gels as microreactors [57,58], and also by strongly polar solvent induced destabilization of a ferrofluid [59].…”
Section: Designed Synthesis Of the Magnetic Corementioning
confidence: 99%
See 2 more Smart Citations
“…While keeping the superparamagnetic behavior, the synthesis of multicore particles proved to be a promising solution for magnetics based imaging, therapeutics, and sensing to improve the manifold magnetic response of particles [40,[52][53][54][55][56]. Magnetic nanoparticle clusters embedded in a polymer shell, to sum the magnetic moments of each nanoparticle, were made applying in situ coprecipitation by using gels as microreactors [57,58], and also by strongly polar solvent induced destabilization of a ferrofluid [59].…”
Section: Designed Synthesis Of the Magnetic Corementioning
confidence: 99%
“…Bio-ferrofluids having multi-core particles [40,52,53,[163][164][165][166] demonstrated an increasing interest for the biomedical area during the last years. The higher particle diameter, still guaranteeing a stable suspension, but without magnetized clumps of particles that are caused by remanence, allows for a more effective collection of the particles by the liver.…”
Section: Rheology and Magnetorheology Of Aqueous Ferrofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The induced displacement of a phantom labeled with 0.4 wt% Ci-MnFe 2 O 4 _0.07 wt% CTAB-GNRs hybrid NPs was significantly greater at around 30.6 ± 4.16 μm than that of 0.4 wt% Ci-MnFe 2 O 4 _0.04 wt% CTAB-GNRs (19.42 ± 2.9 μm) and the sample labeled with 0.4 wt% Ci-MnFe 2 O 4 (8 ± 1 μm). Mehrmohammadi and Yoon et al [ 62 , 63 ] also found that using small nanoclusters of MNPs with a size of 55 nm resulted in higher displacements for pulsed MMUS than using individual MNPs. Hence, a similar outcome was observed in our work by generating nanoclusters, which agrees with Mehrmohammadi and Yoon et al [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mehrmohammadi and Yoon et al [ 62 , 63 ] also found that using small nanoclusters of MNPs with a size of 55 nm resulted in higher displacements for pulsed MMUS than using individual MNPs. Hence, a similar outcome was observed in our work by generating nanoclusters, which agrees with Mehrmohammadi and Yoon et al [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%